1948
DOI: 10.1136/thx.3.2.122
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Costal and Abdominal Pressure on the Action of the Diaphragm in Normal and Emphysematous Subjects

Abstract: The use of pressure on the abdomen by an abdominal belt has been advocated by Christie (1933) and by Alexander and Kountz (1934) for the treatment of emphysema. Warner and Doidge (1939) have employed a costal belt for the same purpose. Both kinds of treatment were successfully used in some patients only, and as it is the aim of the treatment to influence the range of the diaphragm it seemed useful to examine this influence in a number of normal and emphysematous subjects. METHODThe level of the diaphragm was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1949
1949
2003
2003

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Herxheimer [33] studied the effects on the position and excursion of the diaphragm of both an abdominal and a rib-cage belt, in sitting and supine positions, in patients with COPD and asthma, as well as in healthy subjects. During breathing at rest, the application of the abdominal belt resulted in a cranial displacement of the diaphragm, in both patients and healthy subjects.…”
Section: Abdominal Beltmentioning
confidence: 99%
“…Herxheimer [33] studied the effects on the position and excursion of the diaphragm of both an abdominal and a rib-cage belt, in sitting and supine positions, in patients with COPD and asthma, as well as in healthy subjects. During breathing at rest, the application of the abdominal belt resulted in a cranial displacement of the diaphragm, in both patients and healthy subjects.…”
Section: Abdominal Beltmentioning
confidence: 99%
“…It is known that pressure on the abdominal wall displaces the diaphragm upwards (Herxheimer, 1948). It was found that at the same time, in spite of this obstacle to the diaphragmatic movement, the vital capacity decreased only very little.…”
Section: The Effect Of Abdominal Pressurementioning
confidence: 99%
“…Grossmann and Herxheimer (1948) have described a radiological method of measuring this level. They found a lowered diaphragm not only in severe but also in moderate emphysema.…”
Section: Diaphragmatic Action Andmentioning
confidence: 99%